Estimating the economic impact of COVID-19 disruption on access to sexual and reproductive health and rights in Eastern and Southern Africa - Hillary Kipchumba Kipruto; Humphrey Cyprian Karamagi; Solyana Ngusbrhan Kidane; Daniel Mwai; Daniel Mwai; David Njuguna; Benson Droti; Wangui Muthigani; Easter Olwanda; Elvis Kirui; Ayotunde Adenola Adegboyega; Amaka Pamela Onyiah; et al. (Frontiers Media S.A., 2023)
BackgroundThe Coronavirus disease 2019 (COVID-19) resulted in the disruption of Sexual and Reproductive Health Rights (SRHR) services in the Eastern and Southern Africa region. To date, studies estimating the impact of COVID-19 disruptions have mainly focused on SRHR services without estimating the economic implication.MethodWe used national service coverage data on the effectiveness of interventions from the lives saved tool (LiST), a mathematical modeling tool that estimates the effects of service coverage change in mortality. We computed years lost due to COVID-19 disruption on SRHR using life expectancy at birth, number of years of life lost due to child mortality, and life expectancy at average maternal death. We calculated the economic value of the lives saved, using the values of statistical life year for each of the countries, comparing 2019 (pre-COVID-19) to 2020 (COVID-19 era).FindingsThe total life-years lost were 1,335,663, with 1,056,174 life-years lost attributed to child mortality and 279,249 linked to maternal mortalities, with high case-fatality rates in the Democratic Republic of Congo, Burundi, and Tanzania. The findings show COVID-19 disruptions on SRHR services between 2019 and 2020 resulted in US$ 3.6 billion losses, with the highest losses in Angola (USD 777 million), South Africa (USD 539 million), and Democratic Republic of Congo (USD 361 million).ConclusionThe monetized value of disability adjusted life years can be used as evidence for advocacy, increased investment, and appropriate mitigation strategies. Countries should strengthen their health systems functionality, incorporating and transforming lessons learned from shock events.